2018
DOI: 10.3390/su10020483
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Methodologies for the Evaluation of Offer Curves in Energy and Capacity Markets through Energy Efficiency and Demand Response

Abstract: Abstract:The objectives of improving the efficiency, and integration, of renewable sources by are complex in practice and should be linked to an increase of demand-side flexibility. The main challenges to achieving this flexibility are the lack of incentives and an adequate framework. For instance, customers' revenue is usually low, the volatility of prices is high and there is not any practical feedback to customers from smart meters. The possibility of increasing customer revenue could reduce the uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…The results are shown in Table 1. According to Alcalá, the active, reactive, distortion, apparent power P(W), Q(Var), D(VA), and S(VA) are defined by Equation (2). This definition only considers the fundamental harmonic and pays no attention to the additive property.…”
Section: Validation Of Features Additive Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…The results are shown in Table 1. According to Alcalá, the active, reactive, distortion, apparent power P(W), Q(Var), D(VA), and S(VA) are defined by Equation (2). This definition only considers the fundamental harmonic and pays no attention to the additive property.…”
Section: Validation Of Features Additive Propertymentioning
confidence: 99%
“…Therefore, the harmonic current features have good additive property and they are independent of power network states. Alcalá defined the active power (P), reactive power (Q), apparent power (S) and distortion power (D) in Equation (2) with no consideration of their additive property [23]. The authors calculated the power quantities according to Alcalá's definitions and found that only P and Q have good additive property while D and S do not.…”
Section: Validation Of Features Additive Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the authors evaluate the use of DR and PV as energy resources for power planning aiming at sustainable development. The problem in this work is that customers are considered at an aggregated level through demand price elasticity without the consideration of the different characteristics and flexibilities of customer end-uses [29]. In another past paper [30] the authors propose a shifting optimization algorithm for flattening electricity consumption in residential segments for the so-called advanced tariffs (ToU).…”
Section: Literature Surveymentioning
confidence: 99%
“…The granularity of data is fixed from 10 to 20 s for a better evaluation of end-uses and to achieve a customer database with multiple possibilities (see for example REDD database in a past paper [34]). For example, this database has been tested for Non-Intrusive Load Monitoring Methodologies (NIALM) through Smart Meter data, for different purposes and loads (the use of NIALM for the disaggregation of main loads can be found previously [29] and for small nonlinear loads in a past paper [39]). This pacer, for monitoring purposes, is of considerable interest in the case of some water heaters with fast switching because demand cycling ranges from 10 to 30 s in some periods.…”
Section: Customer Descriptionmentioning
confidence: 99%